"Enabling Conditions" in the Conflicts of Acts 1–8:3. Issue 2 (4th May 2017) - Stenschke, Christoph
ABSTRACT: It is possible to identify a number of contested domains in the religious conflicts of Acts 1–8:3, namely the heritage of Israel; the identity, fate and significance of Jesus of Nazareth; the privilege and duty of instructing the people of God; authority in other spiritual matters; legitimate leadership of the people of God; and public recognition/honour. But there are also a number of political, social, economic, cultural, psychological and transcendent enabling conditions on both sides of this conflict which made its course and development possible. An examination of these enabling conditions sheds light on the complexities of intra-religious conflicts in both that context and the present.